THE EFFECT OF COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE CENTRAL STATISTICS AGENCY OF PESAWARAN REGENCY, LAMPUNG PROVINCE - Kautsar, Wahyu Ahmad (University of Sang Bumi Ruwa Jurai, 2025)
Employee performance is an important element that determines the success of an organization, including in government institutions such as the Central Statistics Agency (BPS) of Pesawaran Regency. Improving employee performance is a key factor in achieving organizational goals effectively and efficiently. However, in practice, there are still challenges in the form of differences in competency levels and low work discipline among employees, which can affect the quality and productivity of work. Competence, which includes abilities, knowledge, and work skills, plays an important role in determining the extent to which an employee is able to carry out their duties professionally. On the other hand, work discipline is a form of employee responsibility and compliance with regulations, time, and organizational rules. This study aims to analyze the extent to which competence and work discipline influence employee performance at the BPS in Pesawaran Regency. The research method used was field research with a quantitative approach, in which data was collected through questionnaires and observation. The results of the analysis showed that the Competence variable (X1) had a significant effect on Employee Performance (Y) of 87.2%. Furthermore, the Work Discipline variable (X2) also affects Employee Performance (Y) by 68.6%. Simultaneously, these two variables affect employee performance by 93.3%. These findings indicate that competence and work discipline play a major role in improving employee performance, so they need to be taken into account in human resource development strategies at the Pesawaran Regency BPS.